STRATEGI TIONGKOK MEMASARKAN PRODUK-PRODUK ELEKTRONIK DI INDONESIA TAHUN 2010-2104 - Setiawan, Ade; Harto, Syafri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research is a qualitative research by conducting literature review and compiling data from books, journal and the website. The influx of Tiongkok electronic products in Indonesia give many influence to the internal condition of Indonesia.The entry of Tiongkok electronic products in Indonesia is officially since 2010. Where from legitimate and enactment of ACFTA , free trade throughout Southeast Asian countries and China established . ACFTA is an agreement between China and Southeast Asian countries to make free trade . Can we see now a flood of Tiongkok electronic products with low price and quality in Indonesia .This study shows the various strategies of the Chinese in marketing a wide range of electronic products in Indonesia by utilizing the framework of ACFTA .Keywords : Tiongkok, Indonesia, ACFTA, Free Trade Agreement,ASEAN